If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(6*(5/6)*x)/5 = (5*12)/6 // - (5*12)/6
(6*(5/6)*x)/5-((5*12)/6) = 0
(6*(5/6)*x)/5-10 = 0
x-10 = 0 // + 10
x = 10
x = 10
| 6=m/10 | | .5x^2=.2X+.1 | | 8x/y^2*6y/7x | | a^2-4a-10-2=0 | | (5/7y-3)(5/7y+3)=0 | | (5/7y-3)(5/7y+3) | | 32-r=15 | | 4.1t+21.6=6.43 | | 103-4x=3x+15 | | b^2-20b+64=0 | | y+5/8y^2+y-7 | | 3+x+1+2=14 | | 2(x+1)+3(x-4)=5 | | 6+c=23 | | 5x/(5x+16)(x-3) | | 8y-5-3y^2=0 | | 7x/(7x-18)(x+9) | | 7y-2-5y^2=0 | | 4(3p-5)=5(7-2p) | | d^2+12d+36=0 | | 4x-4=1-(3-x) | | x^3=440 | | -6x-38=10x+26 | | (y-10)2-12=0 | | 4x+1/5=-7 | | 17/2w=5 | | 8/9y=48 | | 3x/4-2=10 | | 6n^2+8=14 | | -50m^3n^5/-5m^2n^2 | | 7a^2+7=259 | | r^3-2r^2+2=0 |